Genesis - Arnold, Bill T. 1955- (Cambridge University Press, 2014)
This commentary is an innovative interpretation of one of the most profound texts of world literature: the book of Genesis. The first book of the Bible has been studied, debated, and expounded as much as any text in history, yet because it addresses the weightiest questions of life and faith, it continues to demand our attention. The author of this new commentary combines older critical approaches with the latest rhetorical methodologies to yield fresh interpretations accessible to scholars, clergy, teachers, seminarians, and interested laypeople. It explains important concepts and terms as expressed in the Hebrew original so that both people who know Hebrew and those who do not will be able to follow the discussion. 'Closer Look' sections examine Genesis in the context of cultures of the ancient Near East. 'Bridging the Horizons' sections enable the reader to see the enduring relevance of the book in the twenty-first century
Keywords: Bible / Genesis / Commentaries; Bibel -- Genesis; Bibel; Kommentar